Evaluation of disc diffusion tests and agar screening for predicting mecA-mediated oxacillin resistance in Staphylococcus lugdunensis revealed a cefoxitin-susceptible, mecA-positive S. lugdunensis clonal complex 27 clone - Pak-Leung Ho; Melissa Chun-Jiao Liu; Man-Ki Tong; Pui-Man Fan; Cindy Wing-Sze Tse; Alan Ka-Lun Wu; Vincent Chi-Chung Cheng; Kin-Hung Chow (Journal of Global Antimicrobial Resistance, 2020)
Objectives: This study evaluated disc diffusion tests and agar screening for detecting mecA-mediated oxacillin resistance in Staphylococcus lugdunensis (S. lugdunensis). Methods: Staphylococcus lugdunensis isolates (n = 179) from diverse sources in Hong Kong during 1998–2018 were investigated by disc diffusion tests (cefoxitin and oxacillin) and inoculation onto oxacillin (1 μg/mL and 2 μg/mL) and chromID methicillin-resistant Staphylococcus aureus (MRSA) agars. The results were compared with mecA PCR as the reference. Isolates with discordant results were further tested by MIC and penicillin-binding protein 2a (PBP2a) assays. Results: Cefoxitin and oxacillin zone diameters were not distributed in ways that allowed reliable division of the mecA-positive (n = 52) and mecA-negative (n = 127) isolates. On applying the 2019 Clinical Laboratory Standards Institute (CLSI) M100 breakpoints for cefoxitin disc results, there was 88% categorical agreement (CA) and 40% very major error (VME). Screening using 2 μg/mL oxacillin agar reliably differentiated mecA-positive and mecA-negative isolates (100% CA) without any major error (ME) or VME results. The performance of screening using 1 μg/mL oxacillin agar or ChromID MRSA agar was variable (74–89% CA, 0–38% ME and 0–37% VME). The mecA-positive isolates (n = 21) that could not be detected by the cefoxitin disc test were further characterised. The cefoxitin MIC for all 21 isolates was ≤4 μg/mL. Twenty isolates had an oxacillin MIC of 1–2 μg/mL and one had an oxacillin MIC of 4 μg/mL. All had positive PBP2a results and were typed as clonal cluster 27/SCCmec V. Conclusions: These findings highlight the need to evaluate phenotypic methods using mecA-positive S. lugdunensis with different oxacillin resistance phenotypes.